2019
DOI: 10.1146/annurev-animal-020518-115250
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on Intermediary Metabolism for a Better Understanding of Nutrition in Teleosts

Abstract: The rapid development of aquaculture production throughout the world over the past few decades has led to the emergence of new scientific challenges to improve fish nutrition. The diet formulations used for farmed fish have been largely modified in the past few years. However, bottlenecks still exist in being able to suppress totally marine resources (fish meal and fish oil) in diets without negatively affecting growth performance and flesh quality. A better understanding of fish metabolism and its regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 161 publications
1
33
0
2
Order By: Relevance
“…Recently, it has been revealed that early nutritional programming exerts several modulating effects on metabolic processes in juvenile/adult fish, making this a promising approach for fish nutrition (Panserat et al, 2019). Particularly, the effects of nutritional programming on carbohydrate metabolism have been intensively studied in aquaculture fish with a low capacity to efficiently use carbohydrates (Geurden et al, 2007(Geurden et al, , 2014Fang et al, 2014;Rocha et al, 2014Rocha et al, , 2015Rocha et al, , 2016aGong et al, 2015;Liang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been revealed that early nutritional programming exerts several modulating effects on metabolic processes in juvenile/adult fish, making this a promising approach for fish nutrition (Panserat et al, 2019). Particularly, the effects of nutritional programming on carbohydrate metabolism have been intensively studied in aquaculture fish with a low capacity to efficiently use carbohydrates (Geurden et al, 2007(Geurden et al, , 2014Fang et al, 2014;Rocha et al, 2014Rocha et al, , 2015Rocha et al, , 2016aGong et al, 2015;Liang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve fish nutrition, it is scientifically challenging to not only search for potential alternative feed ingredients and feed supplementation but also perform research into understanding fish metabolism and how it can be modulated. Recently, several hypothesis-driven scientific approaches for fish nutrition have been demonstrated (Panserat et al, 2019). Nutritional programming is an issue that needs to be explored to examine how it modulates metabolism in fish (Geurden et al, 2007;Fang et al, 2014;Rocha et al, 2014Rocha et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies in fish have revealed how the early environment can have long lasting-effects on the later phenotype and on the ability to adapt to environmental conditions later in life (reviewed by [50]). Such early stimuli refer, among others, to temperature at larval stage [51], cold-shock and air-exposure to embryos and larvae [52], early acute hypoxia at embryo stage, broodstock or fry methionine deficient diets [53], and first feeding with carbohydrates [54], a mix of plant proteins [55] or soya-based diets [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…In murine models, maternal fat intake alters ARA (22:4n-6) and DHA contents in the liver, which was related to the epigenetic regulation of Fads2 gene promoter and the expression of the gene [34]. In fish, epigenetic studies are considered a relatively new area of research [35]. An earlier study showed that there was a negative correlation between the methylation status of the putative promoter region of the fads2 and fads2 gene expression in Japanese sea bass (Lateolabrax japonicus) [36].…”
Section: Introductionmentioning
confidence: 99%